Determinación de glicemia en pobladores adultos de ambos sexos, atendidos en el puesto de salud de Buenos Aires Sur del distrito de Víctor Larco, en diciembre del 2010 - Ramos Benites, Leonila Margarita (2011)
The main goal of the present research work was to determine the glycemic in adult patients of both sexes who were treated in the health center of Buenos Aires Sur in the district of Victor Larco in December 2010. The glucose is the fuel used in great proportion by the specialized cells. Since it is the immediate source of energy to the organism. However there are pathologies in the metabolism of the glucose. For this reason we consider that the determination of the glucose is important in order to prevent the diseases caused by the incorrect metabolism of the glucose in the study group. For this purpose we have applied the enzymatic method which defends that the normal values oscillate between 70 and 110 mg/dl. The results show that the 25.93% of the patients have a low level of glucose, el 70.37% are in the normal range and the 3.70% have a high level. These values are meaningful in comparison with the normal ones. Out of 25.93% with decreased values, the 5.56% are male and the 20.37% are female patients. The main outstanding age in this group oscillates between 57 and 66 years. Out of 70.37% patients with normal values, 48.15% were women and the 22.22% are men. The main outstanding age in this group oscillates between 57 and 66 years. Out of 3.70% patients with increased values, the 3.70% are women and the 0% are men. The main outstanding age in this group oscillates between 37 and 46 years. Therefore we can conclude that in the main patients’ percentage, the levels of glycemic are in normal ranges but exists a considerable patients’ percentage who present hypoglycemic